A methodology to detect abnormal relative wall shear stress on the full surface of the thoracic aorta using four‐dimensional flow MRI. Issue 3 (18th April 2014) - van Ooij, Pim; Potters, Wouter V.; Nederveen, Aart J.; Allen, Bradley D.; Collins, Jeremy; Carr, James; Malaisrie, S. Chris; Markl, Michael; Barker, Alex J.
<x xml:space="preserve">Abstract</x> Purpose To compute cohort‐averaged wall shear stress (WSS) maps in the thoracic aorta of patients with aortic dilatation or valvular stenosis and to detect abnormal regional WSS. Methods Systolic WSS vectors, estimated from four‐dimensional flow MRI data, were calculated along the thoracic aorta lumen in 10 controls, 10 patients with dilated aortas, and 10 patients with aortic valve stenosis. Three‐dimensional segmentations of each aorta were coregistered by group and used to create a cohort‐specific aortic geometry. The WSS vectors of each subject were interpolated onto the corresponding cohort‐specific geometry to create cohort‐averaged WSS maps. A Wilcoxon rank sum test was used to generate aortic P‐value maps (P<0.05) representing regional relative WSS differences between groups. Results Cohort‐averaged systolic WSS maps and P‐value maps were successfully created for all cohorts and comparisons. The dilation cohort showed significantly lower WSS on 7% of the ascending aorta surface, whereas the stenosis cohort showed significantly higher WSS on 34% of the ascending aorta surface. Conclusions The findings of this study demonstrated the feasibility of generating cohort‐averaged WSS maps for the visualization and identification of regionally altered WSS in the presence of disease, compared with healthy controls. Magn Reson Med 73:1216–1227, 2015. © 2014 Wiley Periodicals, Inc.